Service innovation in customer intelligence from ai perspective: A smart framework for tourist customer experiences - Hoang, Duc Sinh (Tạp chí Khoa học HUFLIT, 2021)
This research aims at introducing a theoretical and practical framework for building a customer experience management system based on smart services. The current trends of technologies can help enterprises in the travel industry to know their customers thoroughly, capture and manage customer experience, facilitate customer experience, and to provide intelligent, adaptive, and personalized services to each customer based on the customer experience. The proposed framework extends the current customer experience management by proposing a new facet to represent and manage the customer experience in order to provide smarter services to customers. In general, this framework constructs a customer experience management infrastructure for a tourist company that manages customer experience related to the customer to improve smart service access and usage. In particular, this framework is the starting point to trigger the paradigm shift by elaborating a customer experience management system that provides smart services and integrates those services with traditional customer relationship management.